2018
DOI: 10.1016/j.jsxm.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

S-Nitrosoglutathione Reductase (GSNOR) Deficiency Results in Secondary Hypogonadism

Abstract: Background Excess reactive oxygen species and reactive nitrogen species are implicated in male infertility and impaired spermatogenesis. Aim To investigate the effect of excess reactive nitrogen species and nitrosative stress on testicular function and the hypothalamic-pituitary-gonadal axis using the S-nitrosoglutathione reductase-null (Gsnor−/−) mouse model. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 21 publications
4
16
0
Order By: Relevance
“…We have previously shown that mice lacking the S-nitrosoglutathione reductase (GSNOR) gene showed increased nitrosative stress and exhibited secondary hypogonadism (19). Therefore, in this study we examined if increased NO levels are able to suppress testosterone (T) and luteinizing hormone (LH) in control C57BL/6J mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that mice lacking the S-nitrosoglutathione reductase (GSNOR) gene showed increased nitrosative stress and exhibited secondary hypogonadism (19). Therefore, in this study we examined if increased NO levels are able to suppress testosterone (T) and luteinizing hormone (LH) in control C57BL/6J mice.…”
Section: Resultsmentioning
confidence: 99%
“…A key molecule in the regulation of TME interactions is the ubiquitous nitric oxide (NO) (10)(11)(12). We have previously established the importance of NO in the cardiovascular and immune systems and in male secondary hypogonadism (13)(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…Nitrosative stress is an inhibitor of Leydig cell steroidogenesis function through NO. Experiments examining the impact of NO on steroid biosynthesis in Leydig cells demonstrate that NO administration has an inhibitory effect on steroidogenesis leading to suppressed testosterone levels in mice ( 10 , 33 , 34 ). Research suggests that NO impacts testosterone synthesis directly by inhibiting cholesterol modification, an important precursor to steroid products ( 33 ).…”
Section: Nitroso-redox Imbalance Impairs Testosterone and Luteinizingmentioning
confidence: 99%
“…Research suggests that NO impacts testosterone synthesis directly by inhibiting cholesterol modification, an important precursor to steroid products ( 33 ). However, the hypothalamus-pituitary-gonadal axis remains inducible because administration of GnRH and human chorionic gonadotrophin (hCG) into nitrosatively stressed mice stimulated LH and testosterone, respectively ( 10 ). Thus, nitrosative stress in excess can inhibit testosterone production likely due to hypothalamic-pituitary dysfunction.…”
Section: Nitroso-redox Imbalance Impairs Testosterone and Luteinizingmentioning
confidence: 99%
See 1 more Smart Citation